Pelatihan Aplikasi ZOTERO dalam Upaya Optimalisasi Penulisan Referensi pada Karya Tulis Ilmiah bagi Guru-Guru di Kabupaten Takalar - Mas'ud, Syamsuddin; Ihsan, Hisyam; Tampa, Alimuddin; Sukarna; Ashari, Nur Wahidin (LOSARI DIGITAL, 2023)
This service is conducted in Takalar Regency, South Sulawesi Province. It is motivated by several issues faced by our partners, including the limited knowledge of teachers in utilizing Zotero through Microsoft Word for automatic reference citations, the relatively low awareness of the basic applications for referencing among teachers, and the need for teachers to prepare themselves in creating automated references. Therefore, the objective of this activity is to address these partner-related issues. The methods employed include outreach and teaching, discussions, and collaborative training between the implementers and the partners. The training participants are middle school math teachers from Takalar Regency, members of the Mathematics Subject Teachers' Meeting organization (MGMP Matematika SMP). Through this activity, it is expected that teachers' knowledge in utilizing the Zotero application will increase, raising awareness and understanding among teachers about the importance of flexible and automatic reference application usage, enhancing teachers' insight, abilities, and skills in utilizing Microsoft Word to be more informative and innovative.